Collective Psychological Trauma and Its Impact on Political Transformations in Modern History: An Analytical Study - مشعان, احمد فرحان; عويد, حاتم احمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research explores the phenomenon of collective psychological trauma as a critical yet often overlooked factor in understanding major political and social transformations in modern history, with a special focus on the Arab world. It bridges political psychology and modern historical analysis by examining how large-scale traumatic events—such as wars, occupations, revolutions, and disasters—affect public consciousness, reshape political identity, and influence post-crisis collective behavior. The study begins with the hypothesis that trauma is not merely an individual psychological disruption but a deeply embedded collective experience that alters group memory and national identity. It can lead societies toward either political moderation or extremism, and toward reconciliation or fragmentation, depending on how the trauma is institutionally addressed. The research is structured into three main sections: The first examines the concept and dimensions of collective trauma, and traces its causes in both global and Arab contexts. The second focuses on psychological theories explaining group political behavior post-trauma, such as Social Identity Theory, Cognitive Dissonance, and Social Learning Theory. The third presents case studies and historical models—including the Palestinian Nakba, the September 11 attacks, and the Arab Spring—as well as successful recovery examples from Germany after WWII and South Africa post-apartheid. The study concludes that healing from collective trauma requires genuine transitional justice, neutral institutions, responsible media, and critical education. It emphasizes the need to build new inclusive national narratives based on mutual recognition and constructive memory, not denial. The research ends with practical recommendations for policymakers and scholars working in post-conflict peacebuilding and reconciliation.